Infants born during COVID-19 pandemic experience increased susceptibility to airway hyperresponsiveness - Lachover-Roth, Idit; Cohen-Engler, Anat; Furman, Yael; Rosman, Yossi; Meir-Shafrir, Keren; Mozer-Mandel, Michal; Farladansky-Gershnabel, Sivan; Biron-Shental, Tal; Confino-Cohen, Ronit (Frontiers in Allergy, 2024)
BackgroundAsthma, allergic rhinitis, atopic dermatitis, and food allergy are type 2 inflammation diseases. Since the 1960s, the prevalence of those diseases has steadily increased, presumably due to the “Hygiene hypothesis” which suggests that early exposure of infants to pathogens, siblings, and environmental dust, has a protective effect against the development of allergic diseases. The COVID-19 pandemic increased environmental hygiene due to lockdowns, masks, and social distancing.ObjectiveTo compare the prevalence of allergic diseases among children born before and during the pandemic.MethodsThe Cow's Milk Early Exposure Trial prospectively followed newborns until 12-months of age using monthly survey and examined milk allergy development. Some were born before the first COVID-19 lockdown in Israel (April 2018–March 2020), and some were born during the pandemic (March 2020–May 2021). The monthly surveys included questions regarding atopic comorbidities.ResultsA total of 1,989 infants completed 12-months of follow-up. Among them, 1,086(54.5%) were diagnosed with at least one atopic disease. Among 235 infants born after the last lockdown, 162 were diagnosed with airway hyperresponsiveness (AHR)(68.9%), significantly more than in any other group. No other significant differences were found between the study groups.ConclusionsThere was no significant difference in the development of atopic comorbidities between infants born before and during the pandemic. Significantly more infants who were born after restrictions were eased were diagnosed AHR. A longer follow-up period is needed to obtain a better understanding of the influence of the COVID-19 restrictions on the development of atopic comorbidities. Clinical Trial RegistryNIH Clinical Trials Registry: NCT02785679.